Psychosocial factors are associated with community mobility and participation in persons with dizziness - Pamela M. Dunlap; Jeffrey P. Staab; Patrick J. Sparto; Patrick J. Sparto; Joseph M. Furman; Susan L. Whitney; Susan L. Whitney (Frontiers in Neurology)
IntroductionAmong individuals with dizziness, there is an increased prevalence of psychosocial comorbidity compared to the general population. Increased psychosocial comorbidity among people with dizziness is associated with disability and poorer outcomes in vestibular rehabilitation. However, there is less knowledge regarding the association between psychosocial factors and mobility outcomes in people with dizziness. Therefore, the purpose of this study was to assess the association between psychosocial factors and future activity, participation, and community mobility among people with dizziness. The secondary aim of this study was to explore the constructs measured using patient-reported outcomes associated with psychosocial factors in this population.Materials and methodsWe conducted a prospective cohort study with an in-person baseline assessment and a follow-up assessment completed at 3-months via computerized questionnaires. We measured psychosocial factors at baseline using the Hospital Anxiety and Depression Scale (HADS), the Patient Health Questionnaire 4-item (PHQ-4), the Vestibular Activities Avoidance Instrument (VAAI), and the Dizziness Catastrophizing Scale (DCS). We measured community mobility and participation at baseline and 3-month follow-up using the Life Space Assessment (LSA) and Vestibular Activities and Participation Measure (VAP). To determine the associations between baseline anxiety and depression symptoms, fear avoidance, catastrophizing beliefs and mobility and disability measures, we used simple linear regression and repeated measures ANOVA. We used exploratory factor analysis to identify constructs measured using patient-reported outcomes of psychosocial factors.ResultsThere were 100 participants who completed the baseline assessment [mean age (SD) = 49.2 (15.7) years; 73% female] and 68 participants completed the questionnaire at the 3-month follow-up. In bivariate analyses, baseline VAAI, HADS-A, HADS-D, PHQ-4 depression, and VAP were associated with LSA, and baseline VAAI, HADS-D, PHQ-4 depression, and LSA were associated with VAP at 3-month follow-up (all p < 0.05). In adjusted multivariate analyses, baseline VAP had a large effect (F = 11.65, p = 0.001, η2 = 0.18) and HADS-D had a moderately large effect (F = 4.09, p = 0.048, η2 = 0.07) on LSA score at 3-month follow-up. Baseline VAAI had a large effect (F = 23.35, p < 0.001, η2 = 0.3) on VAP at 3-month follow-up. The exploratory factor analysis of the VAAI, HADS, PHQ-4, and DCS resulted in 4 factors measuring constructs of fear avoidance, anxiety, depression, and catastrophization.DiscussionWe found that baseline psychosocial factors were related to future measures of activity and participation as well as community mobility in people with dizziness. Specifically, baseline activity and participation levels and depressive symptoms were significantly associated with future community mobility and baseline fear avoidance beliefs were significantly associated with future activity and participation. Patient-reported outcome measures of psychosocial factors appear to measure unique constructs, which may indicate that a small number of different outcome measures may be needed to gather important prognostic information to manage individuals with dizziness well.